The mathematical investigation of the work of enzyme biosensors based on conductive polymers (2012)
The work of CP-based biosensors was described mathematically in potentiostatic and potentiodynamic mode with constant voltage was mathematically described. The mathematical models were analyzed by linear-stability theory and bifurcation analysis. The stable-state conditions were derived by using the stable-state requirements for 2-dimensional systems (for the potentiostatic mode) and Routh-Hurwitz criterion (for the potentiodynamic mode). The causes for the oscillatory behavior are the influence of the anodic oxidation of strong reducents forming during the work of the sensor and the formation of the less conductive polymer form (for the potentiodynamic mode). For the case of the presence of autocatalytic stage, its influence is the third oscillations´ cause. The causes of monotonic instability and respective critical values of parameters for potentiostatic mode were also found.